Konflik Kasus Papua dalam Perspektif Hukum Tata Negara Darurat - Nurwidya Kusma Wardhani; Taufiqurrohman Syahuri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to examine how the Papuan conflict from the perspective of emergency constitutional law. The perspective of emergency constitutional law in this study discusses more about the development of the Papuan case from time to time. We all know that the conflict in Papua has yet to be resolved. The role of the TNI and Police in maintaining defense and security in Papua makes its own attention not only in the national arena but also in the international arena. The method of data collection is carried out by means of literacy studies and laws and regulations and conducting qualitative descriptive data analysis to find out how the Papuan conflict from the perspective of emergency constitutional law. Both internal and external threats due to the desire of the Papuan people to separate themselves from Indonesia.